2(5c-9)=

Simple and best practice solution for 2(5c-9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5c-9)= equation:


Simplifying
2(5c + -9) = 0

Reorder the terms:
2(-9 + 5c) = 0
(-9 * 2 + 5c * 2) = 0
(-18 + 10c) = 0

Solving
-18 + 10c = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 10c = 0 + 18

Combine like terms: -18 + 18 = 0
0 + 10c = 0 + 18
10c = 0 + 18

Combine like terms: 0 + 18 = 18
10c = 18

Divide each side by '10'.
c = 1.8

Simplifying
c = 1.8

See similar equations:

| x+25=47 | | 7n+9=58 | | x(-4x-9)=-4 | | 2+2+2+27+4+8+5= | | 2x-8=8+7x | | 8x+6y=168 | | 6x-96=4x+16 | | 10x+6=-4x^2 | | 12x+10y=420 | | (x+1)(x-3)=5 | | 5(t+19)+10=6(t+9)-4t | | a^2+375=0 | | 7x-13=3x-9 | | 12m=7m-5(6+m) | | 4(18-y)+18=12(3+y)-7y | | 53=12-4-5x | | 2x=x+2 | | a^2-375=0 | | 2x^2-11x=-4 | | 2(2-x)+3x=2(x+12) | | 10(6-t)+2=-2(t-3)-7 | | 2x+5=x+11 | | 5(n+1)-10=3n+1 | | 2x^2-7x=3 | | 6(5-w)=2(w+5)+4 | | 19y-17=17y-13 | | -8(21y)= | | 4s-3(s+4)=2(2s+3)+9 | | 52=3x-4+4x | | 3+2+8-3= | | 2(u-13)=4(16-u) | | -1x=-4x^2+3 |

Equations solver categories